(untitled) (International Journal of Nursing Education, 2022)
Background: Obsessive-Compulsive Disorder (OCD) is a common neuropsychiatric disorder thatoccurs across the whole life span and is classified under anxiety disorders. It is a combination ofillogical thoughts and compulsory behaviors caused by anxiety. Aim: To assess obsessive-compulsivedisorder among female nursing students in Alriyada college in Jeddah and its relationship to somevariables. Materials and Methods: A quantitative study “descriptive design”. The total number ofstudy participants was (N =279). Data was collected through one tool by “Arabic Scale of Obsession-Compulsion” (ASOC). Results: The weighted mean for all dimensions of obsessive-compulsive disorderwere 1.5458 ± .36035. The highest mean score of OCD symptoms 1.9023 ± .48364 was related to the“orderliness and discipline” dimension, followed by 1.7513 ± .53314 were related to the “obsessivethoughts” dimension. Conclusion and Recommendations: The study showed a low prevalence ofOCD among study participants. The study recommended early detection, and prevention programs toreduce the negative impact of OCD disorder on the behavior, the mental health of the individual, andsociety. Also, public awareness, screening, and the presence of an educational psychologist in collegemay help for early detection and symptom management.